An amplitude analysis of ππ scattering from new data on the reaction π-p→π+π-n - Corden, M; Dowell, J; Garvey, J; Jobes, M; Kenyon, I; Mawson, J; McMahon, T; Corbett, I; Esterling, R; Lipman, N; Litchfield, P; Sumorok, K; et al. (1979)
We have carried out a partial-wave analysis of ππ scattering in the mass range 1.0 to 2.08 GeV/c2. We find solutions similar to those obtained in previous analyses below 1.8 GeV/c2 but, in addition, we obtain a new solution which does not suffer from violations of unitarity and is compatible with data from other channels. This solution, when continued to 2.08 GeV/c2, shows a g meson with mass and width of 1.734± 0.010 GeV/c2and 0.322±0.035 GeV/c2 respectively, and an h meson with mass 1.935±0.013 GeV/c2and width 0.263±0.057 GeV/c2. The L = 2 partial wave contains the f meson and an additional resonance with parameters m = 1.502±0.025 Gev/c2, Γ = 0.165±0.042 GeV/c2and x = 0.19±0.03. If we associate this state with the f′(1514), our ππ branching fraction is considerably higher than previous determinations. An SU(3) fit to the 2+ nonet yields a mixing angle of 38.4± 1.3°. © 1979.